What Drives Inflows Into Disability? Evidence from Three OECD Countries: Australia, Switzerland, United Kingdom - Llena-Nozal, Ana (OECD Publishing, 2011)
This paper investigates the dynamic effects of health shocks on labour market transitions to disability, employment and other non-employment pathways. It uses longitudinal data to estimate time discrete duration models for three countries: Australia, Switzerland and the United Kingdom. Both current and lagged health status are important predictors of exit to disability benefits and the effect of health problems varies by age group, education and income across countries. The results are robust to the inclusion of different socio-demographic variables and to instrumenting health status
Keywords: Employment; Social Issues/Migration/Health; Australia; Switzerland; United Kingdom